A Fluorescent Indicator for Imaging Lysosomal Zinc(II) with Förster Resonance Energy Transfer (FRET)‐Enhanced Photostability and a Narrow Band of Emission. Issue 2 (7th November 2014) - Sreenath, Kesavapillai; Yuan, Zhao; Allen, John R.; Davidson, Michael W.; Zhu, Lei
Abstract We demonstrate a strategy to transfer the zinc(II) sensitivity of a fluoroionophore with low photostability and a broad emission band to a bright and photostable fluorophore with a narrow emission band. The two fluorophores are covalently connected to afford an intramolecular Förster resonance energy transfer (FRET) conjugate. The FRET donor in the conjugate is a zinc(II)‐sensitive arylvinylbipyridyl fluoroionophore, the absorption and emission of which undergo bathochromic shifts upon zinc(II) coordination. When the FRET donor is excited, efficient intramolecular energy transfer occurs to result in the emission of the acceptor boron dipyrromethene (4, 4‐difluoro‐4‐bora‐3a, 4a‐diaza‐s‐indacene or BODIPY) as a function of zinc(II) concentration. The broad emission band of the donor/zinc(II) complex is transformed into the strong, narrow emission band of the BODIPY acceptor in the FRET conjugates, which can be captured within the narrow emission window that is preferred for multicolor imaging experiments. In addition to competing with other nonradiative decay processes of the FRET donor, the rapid intramolecular FRET of the excited FRET‐conjugate molecule protects the donor fluorophore from photobleaching, thus enhancing the photostability of the indicator. FRET conjugates 3 and 4 contain aliphatic amino groups, which selectively target lysosomes in mammalian cells. This subcellular localization preference was verified by using confocal fluorescence microscopy, which also shows the zinc(II)‐enhanced emission of 3 and 4 in lysosomes. It was further shown using two‐color structured illumination microscopy (SIM), which is capable of extending the lateral resolution over the Abbe diffraction limit by a factor of two, that the morpholino‐functionalized compound 4 localizes in the interior of lysosomes, rather than anchoring on the lysosomal membranes, of live HeLa cells.